2005
DOI: 10.1038/sj.jp.7211409
|View full text |Cite
|
Sign up to set email alerts
|

Communicating with parents of premature infants: who is the informant?

Abstract: Objectives:To determine what sources of information are most helpful for neonatal intensive care unit (NICU) parents, who provides NICU parents with the information, and also what expectations parents have regarding obtaining information.Study design: A 19-item questionnaire was given to the parents of infants 32 weeks or younger prior to discharge from the NICU.Results: Out of the 101 parents who consented, almost all of the parents (96%) felt that 'the medical team gave them the information they needed about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 11 publications
7
57
0
2
Order By: Relevance
“…Actor-family members used statements to ensure that they correctly understood the information provided, such as recapping what the practitioners had said and paraphrasing, more frequently than practitioners. Previous studies have found that clarity and honesty of information is of pivotal importance for families in pediatric 17,22 and neonatal intensive care settings, 23 and is associated with higher parent ratings of the quality of care. Unfortunately, information regarding patient's diagnosis, treatment and prognosis is often not communicated effectively to family members in ICU 24 and NICU.…”
Section: Discussionmentioning
confidence: 99%
“…Actor-family members used statements to ensure that they correctly understood the information provided, such as recapping what the practitioners had said and paraphrasing, more frequently than practitioners. Previous studies have found that clarity and honesty of information is of pivotal importance for families in pediatric 17,22 and neonatal intensive care settings, 23 and is associated with higher parent ratings of the quality of care. Unfortunately, information regarding patient's diagnosis, treatment and prognosis is often not communicated effectively to family members in ICU 24 and NICU.…”
Section: Discussionmentioning
confidence: 99%
“…A significant minority, however, did not understand the seriousness of their infant's acute health problems, even when those health problems were critical and/or lethal. Similar to adult parents in the NICU, 13 many teens told us that they primarily received information about their infant from nurses. They described these conversations as consisting mostly of daily updates, with minimal discussion of the infant's overall condition or management plans.…”
Section: Discussionmentioning
confidence: 99%
“…21 Among the strategies, providing daily bulletins and the daily tracking of the relatives for a professional reference, were highlighted as expectations of mothers and professionals, who understand how tools for the communication of information on the clinical conditions of the child, as well as the need and resource scheduling surgical and therapeutic, because it would facilitate the understanding and the daily monitoring of the child by the mother and the family: Designate a person as a reference and support for the family proved to be highly effective because these people help parents feel less stressed, more informed, confident and prepared for the process of hospitalization and discharge. 22 For the authors, this strategy is coated in benefits for the staff of the NICU and for the quality of care in this environment.…”
Section: " (M 4)mentioning
confidence: 99%